Barriers to adopting a Mediterranean diet in Northern European adults at high risk of developing cardiovascular disease. Issue 4 (21st November 2017) - Moore, S. E.; McEvoy, C. T.; Prior, L.; Lawton, J.; Patterson, C. C.; Kee, F.; Cupples, M.; Young, I. S.; Appleton, K.; McKinley, M. C.; Woodside, J. V.
Abstract: Background: Strong evidence links the consumption of a Mediterranean diet (MD) with a reduced cardiovascular disease (CVD) risk; however, there is uncertainty as to whether non‐Mediterranean regions will adopt this diet. The present qualitative research aimed to investigate attitudes towards a MD in individuals at high CVD risk in a Northern European population. This information is needed to inform development of MD interventions in non‐Mediterranean high‐risk populations. Methods: Focus groups ( n = 12) were held with individuals at high CVD risk from Northern Europe (≥2 CVD risk factors, aged ≥50 years, no established CVD/type 2 diabetes). Attitudes to dietary change towards a MD were explored. Data were analysed using inductive thematic analysis. Results: Sixty‐seven adults participated (60% female, mean age 64 years). There was some awareness of the term MD but limited knowledge of its composition. Barriers to general dietary change were evident, including perception of expense, concern over availability, expectation of time commitment, limited knowledge, lack of cooking skills, amount and conflicting nature of media information on diets, changing established eating habits and resistance to dietary change . Barriers specific to MD adoption were also identified, including perceived difficulty living in a colder climate, perceived impact on body weight, acceptability of a MD and cultural differences . Conclusions: Knowledge of a MD was limited in this Northern European sample at high CVD risk. In addition to general barriers to dietary change, barriers specific to a MD were identified. These findings have implications for the development of interventions aiming to promote MD adoption in non‐Mediterranean populations.